2018
DOI: 10.1073/pnas.1812833115
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective chemoenzymatic glycoengineering of Fab and Fc glycans of a therapeutic antibody

Abstract: The N-glycans attached to the Fab and Fc domains play distinct roles in modulating the functions of antibodies. However, posttranslational site-selective modifications of glycans in antibodies and other multiply glycosylated proteins remain a challenging task. Here, we report a chemoenzymatic method that permits independent manipulation of the Fab and Fc N-glycans, using cetuximab as a model therapeutic monoclonal antibody. Taking advantage of the substrate specificity of three endoglycosidases (Endo-S, Endo-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 35 publications
0
68
0
2
Order By: Relevance
“…We previously characterized the ␣-L-fucosidase AlfC from L. casei (45) and demonstrated that it displays high regiospecific transglycosylation activity that produces 6=FN disaccharide (47). This enzyme constitutes the only characterized bacterial ␣-Lfucosidase acting on ␣-1,6 linkages in core fucosylation structures (core fucosidase), and it was recently employed as a tool for IgG glycoengineering to obtain defucosylated immunoglobulins with enhanced antibody cell-mediated toxicity (51). Core fucosylation of N-glycopeptides and N-glycoproteins has also been attained using L. casei AlfC mutant enzymes (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously characterized the ␣-L-fucosidase AlfC from L. casei (45) and demonstrated that it displays high regiospecific transglycosylation activity that produces 6=FN disaccharide (47). This enzyme constitutes the only characterized bacterial ␣-Lfucosidase acting on ␣-1,6 linkages in core fucosylation structures (core fucosidase), and it was recently employed as a tool for IgG glycoengineering to obtain defucosylated immunoglobulins with enhanced antibody cell-mediated toxicity (51). Core fucosylation of N-glycopeptides and N-glycoproteins has also been attained using L. casei AlfC mutant enzymes (64).…”
Section: Discussionmentioning
confidence: 99%
“…The permease AlfH might also transport more complex substrates, like N-glycosylated peptides derived from the proteolysis of host-and food-derived proteins. Furthermore, the fact that AlfC is able to release L-fucose from core fucosylation of the Fc fragment from immunoglobulins (51) shows that this enzyme has the capacity to hydrolyze ␣-1,6 linkages in polypeptidic substrates and could act on core-fucosylated N-glycopeptides. In this case, after the release of L-fucose by AlfC, amino acids would be removed by PepV to liberate GlcNAc-Asn (Fig.…”
mentioning
confidence: 99%
“…Hitherto, it had been a difficult task to selectively modify Fc or Fab glycans of an intact antibody or a multiply glycosylated protein. Recently, Wang and coworkers (101) reported efficient chemoenzymatic synthesis that allows discriminative glycoengineering of both Fc and Fab glycans of cetuximab, a therapeutic antibody. Cetuximab is a chimeric mouse-human anti-EGFR monoclonal antibody that is widely used for the treatment of colorectal, head, and neck cancers (102).…”
Section: Expanding the Antibody Glycoengineering Toolbox With Endo-s2mentioning
confidence: 99%
“…The mechanism involves preferential binding of Fc to activating-FcγRIIIa (relative to inhibitory-FcγR) on effector cells, as determined by in vitro natural killer cell-based assays. Site-selective glycoengineering of both the Fc and Fab domains of a chimeric anti-epidermal growth factor receptor (EGFR) mAb has recently been shown to lead to increased ADCC activity (76). Future strategies for targeted B cell therapies may further exploit these technological advances by producing engineered mAbs that can potentially enhance B cell killing function and therapeutic efficacy.…”
Section: Perspectives: Advantages Limitations and Future Challengesmentioning
confidence: 99%